Research hotspots and frontiers of glymphatic system and Alzheimer’s disease: a bibliometrics analysis - Liu, Shichao; Zhuang, Lvping; Li, Xiaochun (Frontiers in Aging Neuroscience, 2025)
BackgroundAs a predominant neurodegenerative disorder, Alzheimer’s disease (AD) has garnered increasing attention regarding the association between its pathological mechanisms and glymphatic system (GS) dysfunction.ObjectiveThis study employs bibliometric methods to systematically analyze the evolutionary trajectory and emerging frontiers of GS-AD research from 2010 to 2025, aiming to provide insights for clinical applications and scientific research.MethodsA total of 595 articles were selected from the Web of Science Core Collection. Knowledge mapping was constructed using tools such as CiteSpace and RStudio to analyze country/institutional collaboration networks, co-cited references, and keyword clustering.ResultsOver the past decade, publication output in this field has demonstrated exponential growth. The United States maintains academic dominance, with the University of Rochester and the Nedergaard team serving as central research forces. While China ranks second in publication volume, its international influence requires further enhancement. High-frequency keyword analysis revealed three major research directions: anatomical mechanisms of the GS, (cerebrospinal fluid-interstitial fluid exchange, Aquaporin-4 polarization regulation), pathophysiological associations (amyloid-β/tau clearance, sleep-aging interactions), and clinical translational potential (diffusion tensor image analysis along the perivascular space (DTI-ALPS) imaging biomarkers, targeted intervention strategies). Co-citation analysis indicated that foundational studies by Iliff Jeffrey J and Nedergaard Maiken continue to guide the field, while recent research hotspots concentrate on glymphatic function assessment technologies and cross-disease mechanistic investigations.ConclusionGS research is transitioning from fundamental mechanisms to clinical diagnostics and therapeutics. Future advancements necessitate the integration of multimodal imaging technologies and interdisciplinary collaboration to facilitate early AD diagnosis and therapeutic target development. This study represents the first systematic construction of a knowledge framework for this field, providing theoretical foundations for optimizing research strategies and translational pathways.